Single nuclei RNA sequencing investigation of the Purkinje cell and glial changes in the cerebellum of transgenic Spinocerebellar ataxia type 1 mice - Borgenheimer, Ella; Hamel, Katherine; Sheeler, Carrie; Moncada, Francisco Labrada; Sbrocco, Kaelin; Zhang, Ying; Cvetanovic, Marija (Frontiers in Cellular Neuroscience, 2022)
Glial cells constitute half the population of the human brain and are essential for normal brain function. Most, if not all, brain diseases are characterized by reactive gliosis, a process by which glial cells respond and contribute to neuronal pathology. Spinocerebellar ataxia type 1 (SCA1) is a progressive neurodegenerative disease characterized by a severe degeneration of cerebellar Purkinje cells (PCs) and cerebellar gliosis. SCA1 is caused by an abnormal expansion of CAG repeats in the gene Ataxin1 (ATXN1). While several studies reported the effects of mutant ATXN1 in Purkinje cells, it remains unclear how cerebellar glia respond to dysfunctional Purkinje cells in SCA1. To address this question, we performed single nuclei RNA sequencing (snRNA seq) on cerebella of early stage Pcp2-ATXN1[82Q] mice, a transgenic SCA1 mouse model expressing mutant ATXN1 only in Purkinje cells. We found no changes in neuronal and glial proportions in the SCA1 cerebellum at this early disease stage compared to wild-type controls. Importantly, we observed profound non-cell autonomous and potentially neuroprotective reactive gene and pathway alterations in Bergmann glia, velate astrocytes, and oligodendrocytes in response to Purkinje cell dysfunction.